Republic of Croatia : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
The 2006 Article IV consultation underlies policy issues, including fiscal policy, monetary policy, and structural issues of the Republic of Croatia. Although bank restructuring and privatization have strengthened the financial sector, strong credit expansion and foreign exchange-induced credit risk have raised concerns. To address external vulnerabilities and reduce the burden of the large government on economic growth, Executive Directors recommended more ambitious fiscal consolidation than the authorities' medium-term plans currently envisage. They stressed the urgency of restructuring the loss-making shipyards and removing impediments to privatization.